2016
DOI: 10.1152/ajpendo.00325.2016
|View full text |Cite
|
Sign up to set email alerts
|

Presleep protein ingestion does not compromise the muscle protein synthetic response to protein ingested the following morning

Abstract: Protein ingestion before sleep augments postexercise muscle protein synthesis during overnight recovery. It is unknown whether postexercise and presleep protein consumption modulates postprandial protein handling and myofibrillar protein synthetic responses the following morning. Sixteen healthy young (24 ± 1 yr) men performed unilateral resistance-type exercise (contralateral leg acting as a resting control) at 2000. Participants ingested 20 g of protein immediately after exercise plus 60 g of protein preslee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…We suggest that athletes should aim to ingest sufficient protein intake at every meal to maximize muscle protein synthesis until the next meal. We have recently shown that the ingestion of large amounts of protein in the early post-exercise recovery phase does not compromise the muscle protein synthetic response to protein ingestion at a later stage [29]. This suggests that every meal moment represents a unique opportunity to stimulate muscle protein synthesis and that the muscle protein synthetic response to each meal may be additive.…”
Section: Pre-sleep Protein Feeding As a Strategy To Increase Overnmentioning
confidence: 99%
“…We suggest that athletes should aim to ingest sufficient protein intake at every meal to maximize muscle protein synthesis until the next meal. We have recently shown that the ingestion of large amounts of protein in the early post-exercise recovery phase does not compromise the muscle protein synthetic response to protein ingestion at a later stage [29]. This suggests that every meal moment represents a unique opportunity to stimulate muscle protein synthesis and that the muscle protein synthetic response to each meal may be additive.…”
Section: Pre-sleep Protein Feeding As a Strategy To Increase Overnmentioning
confidence: 99%
“…It is noteworthy that insight into important factors within the exercise prescription that maximizes muscle anabolic potential to feeding have been developed in healthy models. For example, it is necessary to recruit as many muscle fibers as possible to maximize the anabolic action of resistance exercise to subsequent protein intake . In particular, a single bout of resistance exercise performed to elicit maximal muscle fiber activation and, with sufficient volume load (repetitions × load), enhances the dietary amino acid sensitivity of muscle protein synthesis rates to protein intake for at least 1 day in healthy adults …”
Section: Exercise and Nutrition Are Coordinated Stimulimentioning
confidence: 99%
“…For example, it is necessary to recruit as many muscle fibers as possible to maximize the anabolic action of resistance exercise to subsequent protein intake. 52,53 In particular, a single bout of resistance exercise performed to elicit maximal muscle fiber activation and, with sufficient volume load (repetitions × load), 54 enhances the dietary amino acid sensitivity of muscle protein synthesis rates to protein intake for at least 1 day in healthy adults. 52 Further manipulation of exercise prescription is required to potentiate the postexercise muscle protein synthetic response in older adults vs their younger counterparts.…”
Section: E Xercis E and N Utriti On Are Coordinated S Timulimentioning
confidence: 99%
“…The effects of resistive exercise can also be enhanced using nutritional supplements. In combination with muscle protein breakdown and other mechanisms, attenuated rates of muscle protein synthesis are responsible for muscle atrophy in immobilization and a resistance to nutrient‐induced stimulation of protein synthesis has been observed . Paddon‐Jones et al showed that essential amino acids and carbohydrate supplementation during bed rest could preserve lean mass of the lower leg but not strength.…”
Section: Introductionmentioning
confidence: 99%
“…In combination with muscle protein breakdown and other mechanisms, attenuated rates of muscle protein synthesis are responsible for muscle atrophy in immobilization 24,25 and a resistance to nutrient-induced stimulation of protein synthesis has been observed. 26,27 Paddon-Jones et al 28 showed that essential amino acids and carbohydrate supplementation during bed rest could preserve lean mass of the lower leg but not strength. Other bed rest studies did not find any positive effects of protein or essential amino acids supplementation alone on muscle volume or strength loss 5,29 suggesting that the combination of nutritional supplementation with resistive exercise maybe the most promising countermeasure for immobilization induced muscle atrophy.…”
mentioning
confidence: 99%